━━━━━━━☆☆━━━━━━━
▹ Answer
-a - 2b - 9c
▹ Step-by-Step Explanation
(-2a - 4b - 6c) - (-a - 2b + 3c)
Remove parentheses
-2a - 4b - 6c - (-a - 2b + 3c)
Collect like terms
-a - 4b - 6c + 2b - 3c
Final Answer
-a - 2b - 9c
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
Answer: -a - 2b -9c
Step-by-step explanation:
-2a - (-a) = -a
-4b - (-2b) = -2b
-6c - (3c) = -9c
-a - 2b - 9c
Answer:
60m/per minute
Step-by-step explanation:
300/5=60
Hope this helps
Please mark me as brainliest
~Courtney
x² - 6x___= 7
(x - ² = ___
x - 3= +/-___
x-3=__and x-3 =__
Answer:
Step-by-step explanation:
hello :
x² - 6x = 7
x² - 6x+9-9___= 7
(x - 3 )²= __16_
x - 3= +/-_4__
x-3=4__and x-3 =_-4_